2020
DOI: 10.1070/qel17234
|View full text |Cite
|
Sign up to set email alerts
|

Generalised hyper-Ramsey spectroscopy of two-level atoms in an optically dense medium

Abstract: The peculiarities of Ramsey resonance and its sensitivity to the light shift from an optically dense medium of cold atoms are investigated. Different composite pulse protocols for clock spectroscopy, including hyper-Ramsey, modified and generalised hyper-Ramsey schemes, are compared. Error signals change significantly due to the processes of absorption and dispersion in the atomic medium. The dependence of the position of the central fringe resonance with a residual uncompensated light shift of the atomic tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…18a in comparison to the original HR3 π protocol [62]. It has been recently demonstrated that GHR(π/4) and GHR(3π/4) schemes have a strong robustness against residual light-shift coupled to spontaneous emission in an optically dense medium of cold atoms [63]. Indeed, there is a large possibility of unexplored exotic composite pulse protocols for optical clocks due to the richness of the quantum Hilbert space engineering [64] including a manipulation of qubit detunings with opposite sign [65].…”
Section: A Hyper-ramseymentioning
confidence: 99%
“…18a in comparison to the original HR3 π protocol [62]. It has been recently demonstrated that GHR(π/4) and GHR(3π/4) schemes have a strong robustness against residual light-shift coupled to spontaneous emission in an optically dense medium of cold atoms [63]. Indeed, there is a large possibility of unexplored exotic composite pulse protocols for optical clocks due to the richness of the quantum Hilbert space engineering [64] including a manipulation of qubit detunings with opposite sign [65].…”
Section: A Hyper-ramseymentioning
confidence: 99%